FORMULASI GULA AREN DAN JAHE PADA PERMEN LEATHER MENGKUDU SEBAGAI PANGAN FUNGSIONAL - Rika Diananing Putri; Aryo Wibisono; Dody Tri Kurniawan (Universitas Tribhuwana Tunggadewi, 2019)
Functional food is a nutrient that is needed by the body, besides the basic components contained in food. Supporting local resources such as spices, tuber crops, vegetables, fruit and so on. Noni is one of the potentials of local plants that are classified in functional food. Noni fruit is rarely liked because of the pungent aroma. With a touch of food engineering technology, the noni fruit can be used as a processed product in the form of snacks that contain nutrients for the body. This supports the research in making noni fruit products into leather candy that can be liked by the public. Noni leather candy formulation with the addition of palm sugar and ginger in a sequence of 25%, 35% and 10%, 20%, 35%. Stages of research using organoleptic (hedonic) tests on the taste, color, aroma, and texture of noni leather candy, using the two-way ANOVA Complete Randomized Design (RAL) method and continued with the Duncan's Method Range Test (DMRT). Panelists included 40 semi-trained, 60 nontrained. The resulting average in color is 3.82; taste 4,6; aroma of 3.58; texture 3.82. Based on these results, the dominant formulation preferred by panelists is A2J3 (35% palm sugar; 30% ginger) followed by laboratory testing which includes water content using a gravimetry /oven method, the result is 20.82%, ash content using a gravimetry method /furnace the result 3.99%, protein content using the Kjeldahl method /tool with a yield of 4.54%, fat content using the Soxhlet method with a yield of 0.07%, carbohydrate content using the method /tool by difference with a yield of 70.58%, antioxidant activity using DPPH produces 38.35Meg / 100gr and vitamin C content using the LOD titration method resulted in 225.7%.